Integra: Fusing music and technology - Integra (Birmingham Integra project, 2005)
Integra is running a Europe-wide programme of live electronic music activities. They have commissioned composers, organised more than 30 performances and transferred classic pieces from their original technology to more modern platforms. In doing this they aim to inspire people to become involved in live electronic music and demonstrate the vitality of the art form. They are developing a new software environment to make music with live electronics, modernising works that use old technology, commissioning composers and overseeing an exciting programme of performances. Integra brings together six research centres and five new music ensembles and is led by Birmingham Conservatoire at Birmingham CIty University in the UK.